Changes in the landscape of field epidemiology - Ehsan Allah Kalteh; Mohammad Hassan Lotfi; Fatemeh Shakeri Shamsi; Hossein Akhondi (Discover Social Science and Health)
Abstract Aim Field epidemiology plays a critical role in investigating disease outbreaks and public health emergencies. This editorial revisits the evolving landscape of field epidemiology, focusing on the increasing reliance on secondary data and the challenges this shift introduces. Subject and method We distinguish Applied Epidemiology from Field Epidemiology, particularly in the Iranian context, and venture into broader implications where necessary. Emphasis is placed on the expanding use of secondary sources of data, such as electronic health records and vast health databases, along with technological advances that influence field engagement. A comparative table is utilized to describe differences. Result While secondary data improves efficiency and cost-effectiveness, direct field investigation remains irreplaceable in managing emerging diseases, chronic conditions, and environmental threats. The shift is most pronounced in countries like Iran, where technological and institutional transitions have reshaped epidemiological practices. Conclusion A hybrid model combining traditional field investigation with modern data analytics is essential to enhance public health responsiveness and research quality. Policy frameworks and training curricula should reflect this integration.